Aryne Cycloaddition Reactions in the Synthesis of Large Polycyclic Aromatic Compounds (Eur. J. Org. Chem. 27/2013). Issue 27 (11th September 2013) - Pérez, Dolores; Peña, Diego; Guitián, Enrique
Abstract : The cover picture shows a group of honeycomb‐like molecular structures that can be obtained by means of aryne chemistry. For decades these highly reactive molecules have been widely used to synthesize large polycyclic aromatic compounds (PACs) in a straightforward manner. The authors provide an overview of the use of cycloaddition reactions of arynes to synthesize PACs containing five or more fused benzene rings. The structural similarity between PACs and nanographenes has led to an increased interest in these synthetic methodologies. D. García and A. Criado are thanked for their help with the design of the cover picture. Details of this work are presented in the Microreview by D. Pérez, D. Peña et al. onpage 5981 ff.